Process for making 3D NAND flash memory

The electrodepositing and annealing of copper-dopant metal alloys in 3D NAND flash memory devices address the issues of high resistance and non-uniformity in copper diffusion barriers, resulting in improved conductivity and reliability with reduced power consumption.

JP7604756B2Active Publication Date: 2024-12-24MACDERMID ENTHONE INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023521504
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-09
Filing Date
2021-10-08
Publication Date
2024-12-24
Estimated Expiration
2041-10-08

AI Technical Summary

Technical Problem

Current 3D NAND flash memory manufacturing processes face challenges with high resistance and non-uniformity of copper diffusion barrier layers, leading to reduced conductivity and increased electrical resistance, which affects device reliability and power consumption.

Method used

A process involving electrodepositing a copper-dopant metal alloy, such as copper-manganese or copper-zinc, followed by annealing to form a conformal and thinner diffusion barrier layer, which is deposited on insulating surfaces and interfaces, reducing electrical resistance and improving conductivity.

Benefits of technology

The process results in lower electrical resistance, enhanced conductivity, and improved reliability of 3D NAND flash memory devices by using conformal, thinner barrier layers, thereby reducing power consumption and manufacturing complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604756000001
    Figure 0007604756000001
  • Figure 0007604756000002
    Figure 0007604756000002
  • Figure 0007604756000003
    Figure 0007604756000003
Patent Text Reader

Abstract

The present invention relates to a process for fabricating a 3D NAND flash memory, the process comprising a first step of electrodepositing an alloy of copper and a dopant metal selected from manganese and zinc, and a second step of annealing the alloy and demixing the alloy to form a first copper layer and a second layer comprising zinc or manganese.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of three-dimensional NAND flash memory devices and processes for fabricating copper conductors in such devices. [Background technology]

[0002] 3D NAND flash memory is formed by a horizontal stack of alternating conductive metal layers (word lines, numbered in multiples of 8) and insulating layers. The conductor / insulator stack is penetrated throughout its entire height by several vertical polysilicon semiconductor channels (drains), creating an array of three-dimensional memory cells, each cell located at the intersection of a channel and a word line. The word lines are electrically connected to bit lines and source lines. Contact between the bit lines and the polysilicon drains is usually provided by tungsten pads or lines.

[0003] The conductivity and reliability of metal contacts are very important criteria to provide good electron movement in the memory. However, the copper diffusion barrier material that must be placed between the copper and tungsten contact lines has a high resistance and blocks part of the current, which slows down the information transfer rate from the word line to the bit line and reduces the power supply from the copper source line to the word line, increasing battery consumption.

[0004] More precisely, the copper diffusion barrier layer between tungsten and copper in current devices has many drawbacks: the barrier materials used, such as tantalum nitride or titanium nitride, have low adhesion to copper, so a thin layer of tantalum or titanium is usually inserted between the nitride and the copper. On the other hand, the tantalum layer is produced by physical vapor deposition (PVD), so it must be covered with a copper seed layer without breaking the vacuum in the chamber to avoid its oxidation to the highly resistant tantalum pentoxide.

[0005] Therefore, the current process for making copper lines in 3D NAND flash memory is complex, and it would be desirable to provide a much easier to implement process that deposits less material at the interface between the tungsten contacts and the copper, resulting in fewer manufacturing steps.

[0006] There is also a need to provide a process for fabricating 3D NAND flash memory that reduces the electrical resistance between two metal levels and is easy to implement, that is less expensive to manufacture, operates faster, and consumes less power.

[0007] Finally, barrier layers deposited in the prior art, for example by dry processes in the gas phase, do not have a uniform thickness over the entire covered surface, but rather the thickness is higher on concave surfaces or edges. Thus, in the particular case of a tungsten contact placed between a polysilicon channel and a copper bit line, a layer of tantalum nitride or titanium nitride deposited in the gas phase, for example by CVD, is thicker at the bottom of the copper-filled trench, precisely at the point where the current flows. The difference in thickness of the barrier material between the bottom and the walls of the copper trench, and the presence of overhangs at the edges of the trench, reduces the electrical resistance in certain areas and increases the resistance in areas where the current flows, which affects the reliability of the device.

[0008] To solve these problems, it would be desirable to have a thinner, more conductive, and more compliant barrier, maximize the trench fill space, reduce the electrical resistance in the area through which current flows, and increase the reliability of 3D NAND flash memory.

[0009] The present invention meets these various needs by at least partially replacing the highly resistive and non-uniform thickness barrier materials used in the prior art with a conformal, thinner and more conductive barrier layer.

[0010] The present invention also provides a process for depositing copper diffusion barrier material and copper in a single fill step into the trench to create copper bitlines.

[0011] Finally, the present invention allows for the selective formation of a copper diffusion barrier layer on the substantially insulating parts (most often silicon dioxide) and, to a lesser extent, at the interface between the copper and the metal contacts, thereby significantly reducing the resistance between these two metal levels and, consequently, between the copper bitline and the contact connecting it to the polysilicon channel of the 3D NAND flash memory.

[0012] General Description

[0013] The present invention answers these various needs by proposing a process for manufacturing 3D NAND flash memory, which can deposit a copper diffusion barrier layer on an insulating surface in a wet process step, rather than a dry process as in the prior art. The process of the present invention can deposit a dopant metal precursor on the copper diffusion barrier layer during the electrodeposition step of copper forming the word lines. The process uses an electrolyte that contains both copper ions and barrier material dopant metal precursor ions.

[0014] The dry process in the present description can be a process selected from the group consisting of atomic layer deposition (ALD), physical vapor deposition (PVD), and chemical vapor deposition (CVD). The present invention provides a process comprising a first step of electrodepositing an alloy of copper and a dopant metal selected from manganese and zinc, and a second step of annealing the alloy to demix and form a first copper layer and a second layer comprising the dopant metal and / or an oxide thereof. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 shows a perspective view of a prior art 3D NAND flash memory that includes a barrier material based on tantalum nitride or titanium nitride. [Diagram 2]2A-2D show process steps for fabricating copper bitlines for a 3D NAND flash memory according to the prior art. [Diagram 3] 3A-3D show a process for fabricating a 3D NAND flash memory according to the present invention in a "filling" mode. [Figure 4] 4A-4D show a process for manufacturing a 3D NAND flash memory according to the present invention in an "overburden" mode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The process of the present invention is therefore a process for making a 3D NAND flash memory, said process comprising a first step of electrodepositing an alloy of copper and a dopant metal selected from manganese and zinc, said first electrodeposition step consisting of contacting a first surface of a metal layer with an electrolyte comprising copper (II) ions and dopant metal ions, followed by polarization for a time sufficient to cover said first surface with a copper-dopant metal alloy, said first electrodeposition step being followed by a second step of annealing said alloy to demix and form a second layer comprising a first copper layer and said dopant metal and / or its oxide.

[0017] In particular, the first copper layer is intended to form the copper bitlines of the 3D NAND flash memory.

[0018] While prior art electrolytes containing copper(II) ions used to form copper bitlines have a much lower pH, electrolytes containing copper(II) ions and dopant metal ions have the advantage of having a pH between 6.0 and 10.0.

[0019] "Electrodeposition" as used herein is understood to mean any process in which a substrate is electrically polarized and contacted with a liquid containing a metal precursor in order to deposit a metal on its surface. Electrodeposition is carried out by passing an electric current between an anode and the substrate to be coated, constituting the cathode, in an electrolyte containing metal ions.

[0020] According to one embodiment, a copper-manganese or copper-zinc alloy is deposited on the surface of a conductive metal layer, said conductive layer covering a dielectric material, preferably an inorganic oxide, and then the alloy is heat treated to separate the copper from the dopant metal, resulting in a second layer substantially comprising manganese, zinc and / or oxides thereof and a first layer substantially comprising copper.

[0021] By "substantially copper-containing layer" is meant a copper deposit containing less than 1% by weight of impurities, said impurities including any element other than copper.

[0022] "Layer substantially comprising manganese, zinc, and / or oxides thereof" means a deposit containing less than 1% by weight of impurities, said impurities including any compounds other than manganese, zinc, and / or oxides thereof.

[0023] During annealing of the alloy, the alloy demixes to form a thin layer substantially comprising manganese, zinc and / or their oxides, and a layer of copper. This thin layer can then be interposed between the layer of copper and the surface of the dielectric material. If the dielectric material is an inorganic oxide, the atoms of the dopant metal form an oxide with the oxygen atoms present in the dielectric, allowing the formation of a layer with diffusion barrier properties for copper, including, for example, manganese oxide (MnO) or zinc oxide (ZnO).

[0024] Advantageously, the concentration of impurities in the copper deposit formed after annealing of the alloy is less than 1% by weight. Furthermore, the layers substantially comprising manganese, zinc and / or their oxides produced according to the process of the invention have the advantage of being conformal (their thickness preferably varies by less than 10% over their entire surface). They are also very thin, for example ranging from 0.1 nm to 3 nm.

[0025] Thus, it is possible to obtain a copper bit line that is separated from the dielectric material by a thin and regular layer that substantially comprises manganese, zinc, and / or their oxides. The process of the present invention also makes it possible to significantly reduce or even eliminate the thickness of the copper diffusion barrier layer used in the prior art to separate the copper bit line from the electrical contact that connects it to the polysilicon channel.

[0026] According to a particular embodiment of the invention, the metal layer comprises a second surface in contact with a mixed surface including both insulating and conductive regions, said insulating regions being made of a dielectric material and said conductive regions being made of a contact metal selected from tungsten, molybdenum, cobalt, and ruthenium, said contact metal being intended to connect a copper bitline and a polysilicon channel of a 3D NAND flash memory.

[0027] In particular, the dielectric material is selected from silicon dioxide, SiOC, SiOCH, SiN or SiC. According to a preferred embodiment, the dielectric material comprises oxygen. During the second step of annealing the alloy, the dopant metal migrates to the mixed surface, whereby a second layer comprising said dopant metal and / or its oxide can cover at least the insulating region of the mixed surface. In an advantageous embodiment, the second layer comprises an oxide of the dopant metal and performs the function of a copper diffusion barrier.

[0028] According to a first embodiment of the process of the invention, called the "fill" mode, the metal layer is a metal seed layer made of copper, a copper alloy or tantalum, which is deposited in a step prior to the first electrodeposition step in contact with the mixed surface of the insulating and conductive regions. In this case, the first surface of the metal layer is the surface of the seed layer, which can be concave and defines a cavity bounded by the walls and the bottom of the trench. The trench cavity has, for example, an average width of the opening ranging from 15 nm to 700 nm and an average depth ranging from 30 nm to 500 nm. In this first embodiment of the process of the invention, the first step of electrodepositing a copper-dopant metal alloy can be carried out for a time sufficient to fill the cavity with said alloy.

[0029] According to a second embodiment of the process of the present invention, the metal layer is a trench-fill copper deposit, in which a first step of electrodepositing a copper-dopant metal alloy to form an alloy deposit is performed for a time sufficient to cover the trench-fill copper deposit, which may be referred to as an "overburden", and the first copper layer formed as a result of a second annealing step is then polished in a third chemical mechanical polishing step. The trench-fill copper deposit may be formed by any method known to those skilled in the art, and is preferably free of dopant metals selected from manganese and zinc.

[0030] The first copper alloy electrodeposition step of the process of the invention may, for example, use an electrolyte comprising in solution in water: - copper(II) ions in molar concentrations from 1 mM to 120 mM; - a copper ion complexing agent selected from aliphatic polyamines having 2 to 4 amino groups, preferably ethylenediamine, in a molar concentration in which the ratio of molar concentration of complexing agent to molar concentration of copper ranges from 1:1 to 3:1; - ions of metals selected from manganese and zinc in molar concentrations such that the ratio of the molar concentration of copper to the molar concentration of the metal ranges from 1:10 to 10:1; -An electrolyte with a pH of 6.0 to 10.0

[0031] According to a particular embodiment, the electrolyte is obtained by dissolving a salt of copper(II) selected from copper sulfate, copper chloride, copper nitrate and copper acetate, preferably copper sulfate, more preferably copper sulfate pentahydrate, in water. The metal ions can be provided by dissolving an organic salt, preferably a carboxylate salt selected from gluconic acid, mucic acid, tartaric acid, citric acid and xylonic acid. The metal ions are preferably substantially complexed with the carboxylic acid or its carboxylate form in the electrolyte.

[0032] According to a particular feature, the copper ions are present in the electrodeposition composition at a concentration between 1 mM and 120 mM, preferably between 10 mM and 100 mM, and more preferably between 40 mM and 90 mM.

[0033] The copper ion complexing agent consists of one or more compounds selected from aliphatic polyamines having 2 to 4 amino groups (-NH2). Among the aliphatic polyamines that can be used, ethylenediamine, diethylenediamine, triethylenetetramine, and dipropylenetriamine, preferably ethylenediamine, can be mentioned.

[0034] The ratio of the molar concentration of the complexing agent to the molar concentration of the copper ions is comprised between 1:1 and 3:1, preferably between 1.5 and 2.5, and more preferably between 1.8 and 2.2.

[0035] In the electrolyte, the copper ions are substantially in the form of a complex with a complexing agent.

[0036] The metal ions are in a molar concentration ranging from 1:10 to 10:1 molar ratio of copper to metal.

[0037] In a particular embodiment of the present invention, the metal is zinc, in which case the ratio of the molar concentration of copper ions to the molar concentration of zinc ions is preferably 1:1 to 10:1.

[0038] When the metal is manganese, the ratio of the molar concentration of copper to the molar concentration of manganese can range from 1:10 to 10:1.

[0039] The pH of the electrolyte can be between 6.0 and 10.0, more preferably between 6.5 and 10.0. According to a particular embodiment, the pH is, for example, equal to 7.0, and is 6.5 to 7.5, preferably 6.8 to 7.2, depending on the uncertainty of the in situ measurement. The pH of the composition can be adjusted to any desired range by one or more pH-modifying compounds, such as, for example, tetra-alkylammonium salts, such as tetra-methylammonium or tetra-ethylammonium. Tetra-ethylammonium hydroxide can be used.

[0040] There is in principle no restriction on the nature of the solvent (provided that it sufficiently solubilizes the active species in solution and does not interfere with electrodeposition), but it is preferably water. According to one embodiment, the solvent comprises mostly water by volume.

[0041] According to a particular embodiment, the composition comprises copper sulfate at 40 mM to 90 mM, ethylenediamine in a molar ratio to copper of 1.8 to 2.2, and zinc gluconate in a concentration ranging from a molar copper to zinc ratio of 2:1 to 3:1. The pH is preferably about 7.

[0042] The first step of electrodepositing an alloy of copper and a selected metal may include: - contacting the conductive surface of the trench with an electrolyte as described above; - polarizing the conductive surface for a time sufficient to effect deposition of the alloy.

[0043] The manganese content or zinc content in the alloy deposited at the end of the first electrodeposition step is preferably between 0.5 atomic % and 10 atomic %.

[0044] The polarization step is carried out for a time sufficient to form the desired alloy thickness. The conductive surface can be polarized either in galvanostatic mode (constant imposed current), or potentiostatic mode (constant potential imposed, optionally relative to a reference electrode), or in pulsed mode (with current or voltage).

[0045] In a particular embodiment of the process for making a 3D NAND flash memory according to the present invention, a copper-metal alloy is deposited on the surface of a copper layer, which can be a seed layer covering the bottom and walls of the trench etched in a previous step, or a volume of copper that fills the trench and was previously deposited according to a process known by a person skilled in the art.

[0046] In a first embodiment, the alloy is deposited to fill a cavity, which has previously been excavated in a substrate and whose surface is covered with a layer of dielectric material and then optionally with a layer of metallic material, in particular a copper and / or tantalum seed layer (so-called "fill" mode). In this first embodiment, the alloy is deposited on the conductive surface of the trench to be filled.

[0047] In a second embodiment, the alloy is deposited on top of a copper layer filling a cavity opening on the surface of the substrate (so-called "overburden" mode), the conductive surface comprising a portion corresponding to the copper deposit filling the cavity and a portion corresponding to the surface of the substrate where the cavity opens.

[0048] The cavities may have an average width at the opening of from 15 nm to 700 nm and an average depth of from 100 nm to 500 nm.

[0049] In a first embodiment, the process according to the invention makes it possible to achieve a copper filling of excellent quality, free of material defects, and without generating significant amounts of contaminants.

[0050] The surface of the cavity to be filled with the alloy is, for example, a first surface of a metal layer having a second surface in contact with a layer of dielectric material, preferably an inorganic oxide such as silicon dioxide, typically deposited by CVD.

[0051] The seed layer may consist of a single material, such as copper or tantalum, or it may consist of a two-layer assembly including a copper layer and a so-called "liner" layer inserted between the copper layer and the dielectric material to improve adhesion of the copper to the material. The liner may consist of, for example, tantalum, ruthenium, cobalt, titanium, or alloys thereof.

[0052] In a particular embodiment, the metal layer is a copper seed layer having a thickness ranging from 4 nm to 20 nm, or a seed layer consisting of a liner having a thickness of 1 nm and a copper seed layer having a thickness of 5 nm.

[0053] According to a second embodiment, the filling of the cavities was carried out using pure copper, either by physical deposition (PVD, CVD, ALD) or by wet processes (autocatalytic or electrolytic), by any method known by a person skilled in the art. In the sense of the present invention, "pure copper" means copper free of other metallic elements, in particular copper free of zinc or manganese. In particular, "pure copper" in the sense of the present invention can be understood to mean a copper deposit which advantageously contains less than 1 atomic % of elements other than copper. Impurities can in particular include oxygen, carbon, nitrogen.

[0054] The first electrodeposition step may include single or multiple polarization steps, variables which the skilled person knows how to select based on general knowledge, and is carried out at a temperature between 20°C and 30°C.

[0055] It may be performed using at least one polarization mode selected from the group consisting of a lamp mode, a galvanostat mode, and a galvano-pulse mode.

[0056] According to one embodiment, the polarization of the conductive surface is performed in a pulsed mode by applying a current per unit area in the range of 3 mA / cm2 to 25 mA / cm2 at a frequency ranging from 5 kHz to 15 kHz, and performing zero current periods at a frequency ranging from 1 kHz to 10 kHz.

[0057] The conductive surface can be contacted with the electrolyte before or after polarization, preferably before energization.

[0058] The first electrodeposition step is stopped when the alloy deposit covers the plane of the substrate to a thickness of 50 nm to 400 nm, for example 125 nm to 300 nm. The alloy deposit corresponds to an alloy mass deposited within the hollow volume of the cavity without completely filling it, or a combination of an alloy mass filling the entire hollow volume of the cavity and an alloy mass covering the surface of the substrate, or only a mass covering the surface of the substrate and the top of the copper deposit filling the cavity and produced in a step prior to the first electrodeposition step.

[0059] The deposition rate of the copper alloy can be in the range of 0.1 nm / s to 6.0 nm / s, preferably 1.0 nm / s to 3.0 nm / s, and more preferably 1 nm / s to 2.5 nm / s.

[0060] The process of the invention includes a second step of annealing the copper alloy deposit obtained at the end of the first electrodeposition step.

[0061] This annealing heat treatment can be carried out at a temperature between 50° C. and 550° C., preferably under a reducing gas such as 4% H 2 in N 2 .

[0062] The combination of low impurity content and a very low percentage of voids results in a copper deposit having low resistivity.

[0063] During the annealing step, manganese or zinc atoms dissociate from the copper, resulting in the formation of two layers: a first layer substantially comprising copper, and a second layer substantially comprising manganese, zinc, and / or oxides thereof.

[0064] The conductive surface that the electrolyte contacts can be the surface of a metallic seed layer that overlies an insulating dielectric material, itself overlying polysilicon, In this embodiment, manganese or zinc atoms migrate through the seed layer to the interface between the seed layer and the dielectric insulating material during the annealing step.

[0065] The layer substantially comprising manganese, zinc and / or oxides thereof is preferably a continuous conformal layer having an average thickness ranging from 0.5 nm to 2 nm. By "continuous" it is meant that the layer covers the entire surface of the dielectric substrate without being flush. By "conformal" it is meant that the thickness preferably varies by ±10% from its average thickness.

[0066] The total impurity content of the first copper layer obtained by the process of the invention at the end of the second annealing step is advantageously less than 1 atomic %. The impurities mainly include oxygen, followed by carbon and nitrogen. The total carbon and nitrogen content is preferably less than 300 ppm.

[0067] The process of the present invention may include a preliminary step of reducing plasma treatment to reduce the native metal oxides present on the surface of the metal layer. Preferably, the plasma treatment is immediately followed by the first electrodeposition step to minimize reformation of the native oxides.

[0068] The process of the present invention may also include a step of making a metal contact of a contact metal selected from tungsten, molybdenum, cobalt and ruthenium, the contact making step being prior to the deposition of the metal layer described above. This metal contact formation step may be carried out by any method known to those skilled in the art.

[0069] The resulting 3D NAND device using the process of the present invention includes at least one copper diffusion barrier material disposed between the copper and the insulating material, which barrier material can include zinc or manganese.

[0070] In the sense of the present invention, "3D NAND flash memory" refers to vertically integrated memory, such as Bit-Cost Scalable (BiCS) commercial reference memory, Pipe-shape Bit-Cost Scalable (P-BiCS) commercial reference memory, Terabit Cell Array Transistor (TCAT) and Vertical NAND (V-NAND) memory.

[0071] A 3D NAND flash memory according to the prior art, as reproduced in FIG. 1, may include: a silicon substrate 10 covered with a stack 20 of layers lying in a horizontal plane, said stack consisting of alternating silicon dioxide layers 20a and conductive metal layers constituting word lines 20b; - at least one polysilicon channel 30 passing vertically through the stack of layers 20; - at least one copper bit line 40 located in a plane parallel to the stack of layers and located above said stack; a metal contact 50 electrically connecting the polysilicon channel 30 and the copper bitline 40; a charge storage region 60, typically comprising silicon nitride (ONO), separating the polysilicon channel 30 and the wordline 20b; Separating the copper bit lines 40 from the metal contacts 50 is a copper diffusion barrier material 90 , typically comprising tantalum nitride or titanium nitride.

[0072] The present invention provides a method for at least partially replacing the copper diffusion barrier material 90 used in the prior art with another copper diffusion barrier material comprising zinc, manganese or an oxide thereof, thereby increasing the electrical conductivity between the copper bit line 40 and the polysilicon channel. In particular, this process allows the barrier layer 90 of the prior art to be removed. In a particular embodiment, the process of the present invention allows the deposition of a layer comprising a zinc or manganese based material at least on the vertical walls and optionally on the bottom of the copper bit line, the nature of the deposited material can vary depending on the position on the surface of the copper line. For example, the zinc or manganese based material deposited on the walls of the copper line can have a diffusion barrier function for copper. For example, no zinc or manganese based material is deposited on the bottom of the copper line, so that the copper is in contact with the metal contact. Finally, a zinc or manganese based material can be deposited on the bottom of the copper line at the interface with the metal contact, without the layer providing a barrier function. All these options depend on the chemical nature of the deposited zinc or manganese material. In particular, zinc oxide or manganese oxide act as a diffusion barrier for copper when deposited to a sufficient thickness.

[0073] The 3D NAND flash memory of the schematic diagram shown in Fig. 1 can be manufactured in the prior art by a method including two series of steps. The first series of steps makes a metal contact 50 on top of the polysilicon channel 30, the metal contact 50 typically being made of molybdenum, tungsten, cobalt, or ruthenium, most commonly tungsten. According to a specific process of the prior art, the first series of steps in making the metal contact includes: - depositing a silicon dioxide layer by CVD at least on top of the polysilicon channel 30, and then etching the silicon dioxide by lithography to form at least one cavity. - depositing successively on the surfaces of the cavity a seed layer of titanium or tantalum by PVD and a seed layer of a copper diffusion barrier layer, for example of titanium nitride or tantalum nitride, by CVD methods; The cavity is filled with tungsten by -CVD and the excess tungsten deposited is chemically mechanically polished (CMP) to obtain metal contacts 50.

[0074] In a second series of steps of the prior art process, partially illustrated in Figures 2A-2D, copper bitlines are deposited over the metal contacts resulting from the first series of steps.

[0075] The second series of steps consisting of making the copper bit lines 40 on the metal contacts 50 may in particular include: - depositing a layer of silicon dioxide 70 by PECVD on the metal contacts 50, followed by etching at least one trench 80 in said layer of silicon dioxide 70, said etching step flushing the surface of the metal contacts 50a at the bottom of the trenches 80, as shown in FIG. 2A; depositing a copper diffusion barrier layer 90, typically tantalum nitride, by PECVD on the walls and bottom of trench 80, as shown in FIG. 2B; - depositing a copper seed layer 100 by PECVD on the copper diffusion barrier layer 90, as shown in FIG. 2C; This is followed by filling the remaining void volume in the trench with copper by electrodeposition, followed by chemical-mechanical polishing of the excess deposited copper to form copper bitlines 40, as shown in FIG. 2D.

[0076] A particular example of a process for fabricating a 3D NAND flash memory according to the invention is shown in Figures 3A-3C, which show a first variant of the inventive process described above, in which the first step of electrodepositing a copper-dopant metal alloy results in the complete filling of the trench volume.

[0077] In FIG. 3A, a substrate is provided that includes: a stack of layers 20 arranged on a horizontal plane, said stack consisting of alternating silicon dioxide layers 20a and conductive metal layers constituting word lines 20b; - at least one polysilicon channel 30 passing vertically through the stack of layers 20; - a metal contact 50 located on top of the polysilicon channel 30, and a trench cut into the dielectric layer 70 to create a mixed surface including dielectric surfaces 70a at the walls of the trench, dielectric surfaces 70b outside the trench and the surface of the metal contact 50a, said mixed surface being covered with a thin metal layer 101 so as to leave a void volume in the trench 80b.

[0078] As shown in FIG. 3B, at the end of the first electrodeposition step according to the process of the present invention, an alloy 200 of copper and a dopant metal selected from manganese and zinc has been electrodeposited onto the metallic seed layer 101, filling volume 80b.

[0079] In FIG. 3C, the alloy 200 is annealed in accordance with a second step of the process of the present invention to separate the copper and the dopant metal to form a first copper layer 110 filling the trench and a second layer 300 comprising said dopant metal and / or its oxide located at the interface between the dielectric surface 70a and the first copper layer 110.

[0080] 4A-4C show a second variant of the inventive process described above, according to which a first step of electrodepositing a copper-dopant metal alloy is carried out after filling the volume of trench 80b with copper according to the prior art process. In this variant, a prior pure copper filling step fills the trench with copper, for example by electrodeposition, and then a copper-metal alloy is deposited on the trench-filling copper according to the first electrodeposition step described above to form a copper-dopant metal alloy deposit, which is called an "overburden".

[0081] A substrate identical to that shown in FIG. 3A is provided, conforming to that shown in FIG. 4A, and in particular including the metal seed layer 101 in the trench and the void volume 80b.

[0082] As shown in FIG. 4B, this void volume 80b has been filled with a copper deposit 400 by electrodeposition in a manner known to those skilled in the art, for example using an electrolyte containing copper(II) ions that is the same or different from the electrolyte used in the first electrodeposition step, and further containing dopant metal ions, preferably all copper(II) ions.

[0083] In FIG. 4C, an alloy of copper and dopant metal 201 is deposited on copper deposit 400 at the end of the first electrodeposition step according to the process of the present invention.

[0084] The alloy 201 is then annealed by a second step according to the process of the present invention to anneal and demix the alloy, forming a first copper layer 111, including the volume of copper contained in the seed layer 101 and the volume of copper that was part of the alloy 201, as shown in Figure 4D. This annealing also allows the formation of a second layer 301 including a dopant metal and / or its oxide located at the interface between the dielectric surfaces (including the dielectric surfaces 70a and 70b) and the first copper layer 111. The second layer including a dopant metal and / or its oxide may or may not cover the surface 50a of the metal contact 50. In Figure 4D, the silicon dioxide of the dielectric 70 and the second layer 301 including a dopant metal including zinc oxide or manganese oxide do not cover the surface of the metal contact 50a.

[0085] The process of the invention is advantageously intended for the creation of copper bit lines for the manufacture of 3D NAND devices and may include, prior to the first electrodeposition step, the steps of creating a polysilicon channel, creating a word line and creating metal contacts, which steps are carried out according to methods known to those skilled in the art. According to an advantageous embodiment of the process of the invention, at least one step of depositing a copper diffusion barrier material, which is carried out in the prior art by a dry process, is replaced by a step of depositing an alloy of copper and a dopant metal selected from zinc or manganese, the deposition step following the first electrodeposition step described above.

[0086] The process of the present invention may include, prior to the first step of electrodepositing the copper-metal alloy: - depositing a layer of silicon dioxide; - etching said layer to form at least one cavity having side walls made of silicon dioxide and a bottom made of metal contact material; - depositing a metal seed layer of copper, or a combination of a metal adhesion layer (known as a "liner") and a copper layer, on the walls and bottom of the cavity;

[0087] Another subject of the invention is the use of zinc or manganese in a process for making a 3D NAND flash memory to inhibit the intercalation of a copper diffusion barrier material (generally highly resistive) between a metal contact and a copper bit line, said barrier material being deposited by a dry process and being selected, for example, from tantalum nitride and titanium nitride, said metal contact electrically connecting, in the 3D NAND flash memory, the polysilicon channel and the copper bit line and comprising a contact metal selected from tungsten, molybdenum, cobalt and ruthenium. The invention is illustrated by the following examples.

[0088] Example 1: Electrodeposition and annealing of copper-zinc alloy to fill cavities covered with tantalum / copper seed layer and overhang of tungsten contact On the tantalum / copper seed layer, 300 nm wide and 600 nm deep trenches were filled with a copper-zinc alloy by electrodeposition. The deposition was carried out using a composition containing a sulfur salt of copper(II) ions and an organic salt of zinc(II) ions at pH 7 in the presence of ethylenediamine.

[0089] A.- Materials and equipment: substrate: The substrate used in this example consisted of a 4x4 cm silicon coupon into which a 300 nm wide, 600 nm deep trench was etched. On the sidewalls, the silicon is covered with silicon oxide and also covered with a thin layer of 1 nm thick tantalum, in contact with a 5 nm thick layer of copper metal. At the bottom of the trench, the silicon is covered with a thick layer of tungsten, in contact with a 5 nm thick layer of copper metal. The resistivity of the substrate is measured to be approximately 30 ohms / square. Electrodeposition solution: In this solution, copper is dissolved in 16 g / L CuSO4(H2O)5 (64 mM Cu 2+ ) and 2 molar equivalents of ethylenediamine. Zinc was provided by zinc gluconate, 25 mM Zn 2+ Tetraethylammonium hydroxide (TEAH) is added to adjust the pH of the solution to 7. Device: In this example, an electrodeposition device was used that consisted of two parts: a cell holding the electrodeposition solution with a fluid recirculation system that controlled the fluid dynamics of the system, and a rotating electrode with a sample holder suitable for the size of the coupons used (4 cm x 4 cm). The electrodeposition cell had two electrodes: a copper anode, and a silicon coupon coated with a copper metal layer that constituted the cathode. A reference was connected to the anode. A connector allowed electrical contact of the electrodes, which were connected by wires to a potentiostat providing a maximum of 20 V or 2 A.

[0090] B.- Experimental Protocol: Preliminary steps: The substrates generally do not require any special treatment unless the wafer is very old or the original copper oxide layer has been too affected by poor subsequent storage, which is usually done under nitrogen. In this case, a plasma containing hydrogen must be applied, either pure hydrogen or a mixture containing 4% hydrogen in nitrogen. First step of electrodeposition: The cathode is 10 mA (or 1.4 mA / cm 2 ) ~ 200mA (or 28.6mA / cm 2 ) current range, e.g. 150mA (or 21.4mA / cm 2 ) in galvano-pulse mode, with pulse durations ranging from 5 to 1000 ms for cathodic polarization and 5 to 1000 ms for zero polarization between two cathodic pulses. This step was performed for 5 min under rotation at 60 rpm. Second annealing step: Annealing was performed at 100° C. for 30 min and then at 350° C. for 15 min in a hydrogen atmosphere (4% hydrogen in nitrogen) to induce migration of zinc to the sidewalls of the trenches at the SiO 2 / copper interface.

[0091] C-Results obtained: Transmission electron microscopy (TEM) analysis performed after annealing reveals perfect filling of the trench wall holes, reflecting good copper nucleation, and the absence of holes in the structure. The thickness of the copper layer on the structure is 200 nm. XPS analysis before annealing shows a homogeneous presence of about 2 atomic % zinc in the alloy. The same type of analysis shows, after annealing, migration of zinc both to the SiO2-Ta interface and to the top surface on the one hand, but not to the W-copper interface. On the other hand, the total contamination in oxygen, carbon and nitrogen does not exceed 600 atomic ppm. This integration has the advantage of reducing the line resistance and optimizing the memory.

[0092] Example 2: Electrodeposition and Annealing of Copper-Zinc Alloy to Fill Cavities Covered with Copper Seed Layer and Overhanging Tungsten Contacts Trenches 300 nm wide and 600 nm deep were filled with copper-zinc alloy by electrodeposition onto a copper seed layer deposited directly on SiO2. The deposition was carried out using a composition containing a sulfur salt of copper(II) ions and an organic salt of zinc(II) ions at pH 7 in the presence of ethylenediamine.

[0093] A.- Materials and equipment: substrate: The substrate used in this example consisted of a 4x4 cm silicon coupon into which a 300 nm wide, 600 nm deep trench was etched. On the sidewalls, the silicon is covered with silicon oxide, which is in direct contact with a 5 nm thick layer of copper metal. At the bottom of the trench, the silicon is covered with a thick layer of tungsten, which is in contact with a 5 nm thick layer of copper metal. The resistivity of the substrate is measured to be approximately 30 ohms / square. Electrodeposition solution: The electrodeposition solution used was the same as in Example 1. Device: The apparatus used was the same as in Example 1.

[0094] B.- Experimental Protocol: Preliminary steps: The substrate does not require any special treatment. The first step of alloy electrodeposition: It is the same as that in Example 1. Second annealing step: The annealing was the same as in Example 1.

[0095] C-Results obtained: Transmission electron microscopy (TEM) analysis performed after annealing reveals perfect filling of the trench wall holes, reflecting good copper nucleation, and the absence of holes in the structure. The thickness of the copper layer on the structure is 200 nm. XPS analysis before annealing shows a uniform presence of about 2 atomic % zinc in the alloy. The same type of analysis shows a more significant migration of zinc to the SiO2-Cu interface after annealing than in Example 1. This integration is ideal for reducing line resistance and optimizing memory.

[0096] Example 3: After filling the structure with copper, a copper-zinc alloy is electrodeposited and annealed to obtain a 300 nm so-called "overburden" deposit that overhangs the tungsten contacts. The 300 nm wide and 600 nm deep trenches were filled with copper by electrodeposition onto a copper seed layer. The deposition was carried out using a composition containing ethylenediamine and the sulfur salt of copper(II) ions of thiodiglycolic acid at pH 7. A 300 nm thick overburden of copper-zinc alloy is then electrodeposited onto the copper deposited in the first step. The overburden is created with a composition containing a sulfur salt of copper(II) ions and an organic salt of zinc(II) ions in the presence of ethylenediamine, at pH 7. A.- Materials and equipment: substrate: The substrate used was the same as in Example 2. Electrodeposition solution: Copper first solution: In this solution, copper is 16 g / L CuSO4(H2O)5 (64 mM Cu) with 2 molar equivalents of ethylenediamine and 50 ppm of thiodiglycolic acid for trench filling. 2+ ) TEAH is added and the pH of the solution is adjusted to 7. Second solution of copper and zinc for overburden: Copper was added in 16 g / L CuSO4(H2O)5 (64 mM Cu) with 2 molar equivalents of ethylenediamine. 2+ Zinc was provided by 25 mM Zn 2+ The pH of the solution is adjusted to 7 by adding TEAH.

[0097] Device: The apparatus used was the same as in Example 1. B.- Experimental Protocol: Preliminary steps: The substrate does not require any special treatment. 1-Copper Filled The process is carried out as follows: 20 mA (or 1.4 mA / cm 2 ) ~ 120mA (or 17.1mA / cm 2 The cathode was polarized in a ramp mode with a current range of 20 mA (or 2.9 mA / cm 2 ) ~ 100mA (or 14.3mA / cm 2 ) with a slope of 0.5 to 2 mA / s.

[0098] 2- The first electrolytic step in which the alloy is deposited to form the overburden The conditions are the same as those in Example 1. 3- Second step of annealing: The annealing was the same as in Example 1.

[0099] C-Results obtained: Transmission electron microscopy (TEM) analysis performed after annealing reveals perfect filling of the trench wall holes, reflecting good copper nucleation, and the absence of holes in the structure. The thickness of the copper layer on the structure is 300 nm. XPS analysis before annealing shows that in the thick copper layer, about 2 atomic % zinc is present uniformly in the alloy. In the structure, the copper is pure. On the other hand, the same type of analysis after annealing shows the migration of zinc through the pure copper, reaching the SiO2-Cu interface and reaching the extreme surface. Meanwhile, the total contamination of oxygen, carbon and nitrogen does not exceed 600 atomic ppm. This solution has the advantage of working with thinner trenches.

[0100] Example 4: Electroplating and Annealing of Copper and Zinc Alloy to Fill Cavities Covered with Copper Seed Layer and Overhanging Nickel-Boron Contacts A 300 nm wide and 600 nm deep trench was filled by electrodeposition with an alloy of copper and zinc on a copper seed layer deposited directly on SiO2. The deposition was carried out using a composition containing a sulfur salt of copper(II) ions and an organic salt of zinc(II) ions at pH 7 in the presence of ethylenediamine. A.- Materials and equipment: substrate: The substrate used in this example consisted of a 4x4 cm silicon coupon on which was etched a trench 300 nm wide and 600 nm deep. On the sides, the silicon is coated with silicon oxide, which is in direct contact with a 5 nm thick layer of copper metal. At the bottom of the trench, the silicon is covered with a thick layer of NiB, which is in contact with the 5 nm thick layer of copper metal. The measured resistivity of the substrate is about 30 Ohms / square. Electrodeposition solution: The electroplating solution used is the same as in Example 1. Device: The apparatus used is the same as in Example 1. B.- Experimental Protocol: Preliminary steps: The substrate does not require any special treatment. 1-First electrolysis step The conditions are the same as those in Example 1. 2- Second step of annealing: The annealing was the same as in Example 1. C-Results obtained: Transmission electron microscopy (TEM) analysis performed after annealing reveals perfect filling of the trench wall holes, indicating good copper nucleation, and the absence of holes in the structure. The thickness of the copper layer on the structure is 200 nm. XPS analysis before annealing shows the presence of about 2 atomic % zinc in the alloy. The same type of analysis after annealing shows that the migration of zinc has occurred to the SiO2-Cu interface and that there is no migration to the NiB-Cu interface.

[0101] Example 5: After filling the structure with copper, a copper-zinc alloy is electroplated and annealed to produce a 300 nm so-called "overburden" deposit that overhangs the nickel-boron contact. On the copper seed layer, a 300 nm wide and 600 nm deep trench was filled with copper by electrodeposition. The deposition was carried out using a composition containing ethylenediamine and the sulfur salt of copper(II) ions of thiodiglycolic acid at pH 7. A 300 nm thick overburden of copper-zinc alloy is then electrodeposited onto the copper deposited in the first step. The overburden is prepared using a composition containing a sulfur salt of copper(II) ions and an organic salt of zinc(II) ions at pH 7 in the presence of ethylenediamine. A.- Materials and equipment: substrate: The substrate used is the same as in Example 3. Electrodeposition solution: The two solutions used are the same as in Example 4. Device: The apparatus used is the same as in Example 1. B.- Experimental Protocol: This is the same as in Example 1. C-Results obtained: Transmission electron microscopy (TEM) analysis performed after annealing reveals perfect filling of the trench wall holes, indicating good copper nucleation, and the absence of holes in the structure. The thickness of the copper layer on the structure is 300 nm. XPS analysis before annealing shows that the copper in the structure is pure, with a uniform presence of about 2 atomic % zinc in the alloy layer. On the other hand, the same type of analysis after annealing shows the migration of zinc through the pure copper, reaching the SiO2-Cu interface and reaching the extreme surface. On the other hand, the Cu-NiB interface is unchanged with no trace of Zn in the NiB. On the other hand, the total contamination of oxygen, carbon and nitrogen does not exceed 600 atomic ppm. This solution has the advantage of producing copper lines with finer dimensions than the prior art.

Claims

1. A process for fabricating a 3D NAND flash memory, the process comprising: (a) electrodeposition of an alloy of copper and a dopant metal selected from manganese and zinc by contacting a first surface of a metal layer (101, 400) with an electrolyte containing copper(II) ions and dopant metal ions, followed by polarization for a time sufficient to cover said first surface with a copper-dopant metal alloy (200, 201); (b) annealing the alloy to demix and form a first copper layer (110, 111) and a second layer (300, 301) comprising the dopant metal and / or its oxide; the metal layer (101, 400) has a second surface in contact with a mixed surface including insulating regions (70a, 70b) and conductive regions (50a), the insulating regions (70a, 70b) being made of a dielectric material; the conductive region (50a) is made of a contact metal selected from tungsten, molybdenum, cobalt, and ruthenium; the contact metal connects a copper bitline (40) and a polysilicon channel (30) of the 3D NAND flash memory.

2. 2. The process of claim 1, wherein the first copper layer (110, 111) forms the copper bitlines of the 3D NAND flash memory.

3. 2. The process of claim 1, wherein the electrolyte containing copper(II) ions and dopant metal ions has a pH of 6.0 to 10.

0.

4. 2. The process of claim 1, wherein during the annealing step, the dopant metal migrates to the mixed surface and the second layer (300, 301) comprising the dopant metal and / or its oxide covers at least the insulating regions (70a, 70b) of the mixed surface.

5. The process of claim 4, wherein the second layer (300, 301) comprises an oxide of the dopant metal and acts as a copper diffusion barrier.

6. 2. The process of claim 1, wherein the metal layer (101) is a metal seed layer of copper, a copper alloy, or tantalum, the metal seed layer being deposited in contact with the mixed surfaces of the insulating regions (70a, 70b) and the conductive regions (50a) in a step prior to the electrodeposition step.

7. The process of claim 6, wherein a portion of the first surface (101a) of the metallic seed layer is concave and defines a cavity (80b) bounded by a wall and a bottom of a trench.

8. The process of claim 7, wherein the trench hollow (80b) has an average opening width ranging from 15 nm to 700 nm and an average depth ranging from 30 nm to 500 nm.

9. The process of claim 7, wherein the electrodeposition step is carried out for a time sufficient to fill the cavity (80b) with the alloy (200).

10. The method of claim 1, wherein the metal layer (400) is a trench-fill copper deposit; said electrodeposition step being carried out for a time sufficient to cover said trench-fill copper deposit (400) to form an alloy deposit (201); 2. The process of claim 1, wherein the first copper layer (111) is formed as a result of an annealing step and is subsequently polished with a chemical mechanical polishing step.

Citation Information

Patent Citations

  • Semiconductor device and its fabrication process

    JP2007012922A

  • Self-forming barrier layer in copper metallization and integration of ruthenium metal liner

    JP2017143266A

  • Electroplating solution, electroplating method and electroplating film

    JP2018119169A

  • Integrated circuit device with layered trench conductors

    JP2018164077A

  • Self-forming barrier process

    JP2020526031A